Factors associated with the need for physical rehabilitation in pedestrian survivors of traffic accidents in Peru, 2016 - 2021 - Roman-Lazarte, Victor (2023)
Introduction. Traffic accidents (TA) are a public health problem worldwide, with an estimated 1.3 million deaths per year from collisions and leaves traumatic sequels in the survivors. Of the total number of victims affected in an AT, injured pedestrians represent 22%. The objective of this study was to determine the factors associated with the requirement of physical rehabilitation of pedestrians injured by any TA in the Peruvian territory. Methods. An observational cross-sectional study was carried out with the data provided by the National Center for Epidemiology, Prevention, and Control of Diseases (CDC Peru) through epidemiological records. A regression analysis was performed, and prevalence ratios (PR) were reported, having the rehabilitation requirement as a dependent variable. Results. A total of 14,186 records of pedestrians injured by being hit by a motor vehicle on the road between 2016 and 2021 were analyzed. 87.89% of the victims did not require post-event rehabilitation. There is a greater probability of rehabilitation if the injured person is older and if the time of the accident occurred between 00:00 and 05:59 hours of the day. There is a lower probability of rehabilitation if the accident is caused by a minor motor vehicle. Conclusions. Many young people and adults are injured; however, older age is a factor associated with the need for rehabilitation, likewise, the type of road and the type of vehicle responsible influence the outcome of the victim.